2016
DOI: 10.1097/mop.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviruses in the early 21st century

Abstract: Purpose of review Enteroviruses cause a wide variety of diseases with neurologic, respiratory, skin, and gastrointestinal findings. The purpose of this review is to clarify changes in the classification of enteroviruses, provide information about recent disease outbreaks, and to summarize progress toward treatment and prevention of these infections. Recent findings Enteroviruses are now classified into 4 distinct species. New variants of Coxsackievirus B1, Enterovirus-A71, and Enterovirus-D68 (EV-D68) have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(59 citation statements)
references
References 51 publications
2
56
0
1
Order By: Relevance
“…Past failures to culture RV from blood might be explained by the predominance of RV-C in viremia (see below), which is known to not grow well in conventional cell lines [18]. With some recent exceptions [19, 20], acute RV infections have rarely been associated with disseminated disease, unlike EVs, where viremia can lead to infection of multiple sites with varied clinical manifestations [21]. However, blood detection of RV by RT-PCR may only represent identification of RV RNA and not true viremia with viable virus.…”
Section: Discussionmentioning
confidence: 99%
“…Past failures to culture RV from blood might be explained by the predominance of RV-C in viremia (see below), which is known to not grow well in conventional cell lines [18]. With some recent exceptions [19, 20], acute RV infections have rarely been associated with disseminated disease, unlike EVs, where viremia can lead to infection of multiple sites with varied clinical manifestations [21]. However, blood detection of RV by RT-PCR may only represent identification of RV RNA and not true viremia with viable virus.…”
Section: Discussionmentioning
confidence: 99%
“…Abzug et al [17] also demonstrated that neutralization of EVs using 750 mg/kg IVIG can change the course of encephalitis with rapid cessation of viremia and can improve the prognosis. Moreover, other studies [12,15,19,25,26] have also reported the use of IVIG for prevention of possibly fatal cases of neonatal HPeV infection. Further studies are required on the use of IVIG in the treatment of HPeV infection to improve the infantile HPeV/EV management protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Enteroviruses are nonenveloped, single‐stranded, positive‐sense RNA viruses belonging to the family Picornaviridae that infect worldwide populations, especially infants and young children . Enteroviruses can cause a variety of clinical illnesses, including acute hemorrhagic conjunctivitis, aseptic meningitis, undifferentiated rash, myocarditis, and neonatal sepsis‐like disease . Human enterovirus serotypes include four species (enterovirus A, B, C, and D), categorized by sequence differences, genome organization, and biological properties .…”
Section: Introductionmentioning
confidence: 99%